Gambaran Sikap Mencari Bantuan pada Mahasiswa Tingkat Akhir di Bandung Raya - Aldela Silmi; Nugraha, Suci (Bandung Conference Series: Psychology Science, 2024)
Abstract. The phenomenon of mental health problems among university students in Indonesia is increasing. This increasing problem is not matched by the search for and use of psychological professional help. This can have a significant impact on students' lives. This study aims to describe the help-seeking attitudes of final-year students who have had suicidal ideation in Greater Bandung. This study used a descriptive method with a quantitative approach. Data were collected using the Attitudes Toward Seeking Professional Psychological Help Short Form (ATSPPH-SF) measuring instrument adapted to Indonesian version by Nurdiyato et al. (2021). This study involved 113 active final-year university students who have had suicidal ideation in Greater Bandung, with 57 males and 56 females. The sample was taken using non-probability sampling method with snowball sampling technique. The results show that final-year students who have had suicidal ideation have a moderate help-seeking attitude. The type of problem that considered the most severe for students is academic problems and the most likely source of help sought is a psychiatrist. Abstrak. Fenomena masalah kesehatan mental pada mahasiswa di Indonesia semakin meningkat. Masalah yang meningkat ini tidak diimbangi dengan pencarian dan penggunaan bantuan profesional psikologis. Hal ini dapat berdampak secara signifikan pada kehidupan mahasiswa. Penelitian ini bertujuan untuk menggambarkan sikap mencari bantuan pada mahasiswa tingkat akhir yang pernah memiliki ide bunuh diri di Bandung Raya. Penelitian ini menggunakan metode deskriptif dengan pendekatan kuantitatif. Data diambil menggunakan bantuan alat ukur Attitudes Toward Seeking Professional Psychological Help Short Form (ATSPPH-SF) yang diadaptasi ke dalam Bahasa Indonesia oleh Nurdiyato et al. (2021). Penelitian ini melibatkan 113 mahasiswa aktif tingkat akhir yang pernah memiliki ide bunuh diri di Bandung Raya, dengan jumlah 57 laki-laki dan 56 perempuan. Sampel diambil menggunakan metode non-probability sampling dengan teknik snowball sampling. Hasil menunjukan bahwa mahasiswa tingkat akhir yang pernah memiliki ide bunuh diri memiliki sikap mencari bantuan pada kategori moderat. Jenis masalah yang dinilai paling berat bagi para mahasiswa adalah masalah akademik dan sumber bantuan yang paling mungkin dicari adalah ahli jiwa.